Fast across all distances: Genetic parameters and selection for racing time in Quarter Horses using a random regression model - Franco, Thiago G.B.; Bignardi, Annaiza B.; Faria, Ricardo A.S.; Silva, Antônio R.; Silva, Josineudson A.II V. [UNESP]; Santana, Mário L. (Elsevier, 2025)
The Quarter Horse, renowned for its exceptional speed and versatility, is one of the most prominent breeds in short-distance racing. Despite this, there is a lack of studies on the performance of these animals across different distances, particularly using an approach that accounts for the longitudinal nature of racing performance. Our objectives in this study were to apply a random regression model (RRM) to estimate genetic parameters for racing time (RT) at different distances in Brazilian Quarter Horses and to examine the genetic trends in performance over recent years. A total of 21,173 records from 4,482 horses that competed in races of varying distances were used. The heritability and repeatability estimates ranged from 0.05 ± 0.02 to 0.22 ± 0.03 and from 0.17 ± 0.02 to 0.48 ± 0.04 for shorter to longer distances, respectively. The genetic correlations for RT between different race distances were very high and positive, with the lowest correlation observed between the 275 m and 402 m distances (0.84 ± 0.12). The RRM effectively identified animals with stable and variable genetic merit across distances. Genetic trends for RT were favorable across races of all distances. Selecting for RT in longer distances may enhance speed across all distances. This longitudinal evaluation proved effective for analyzing performance, revealing important genetic progress in the Brazilian Quarter Horse population, particularly in 402 m races.
Keywords: Genetic correlation; Heritability; Racehorse; Speed; Trend